2016
DOI: 10.1186/s40634-016-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foot landing position on biomechanical risk factors associated with anterior cruciate ligament injury

Abstract: BackgroundIdentification of biomechanical risk factors associated with anterior cruciate ligament (ACL) injury can facilitate injury prevention. The purpose of this study is to investigate the effects of three foot landing positions, “toe-in”, “toe-out” and “neutral”, on biomechanical risk factors for ACL injury in males and females. The authors hypothesize that 1) relative to neutral, the toe-in position increases the biomechanical risk factors for ACL injury, 2) the toe-out position decreases these biomechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The aforementioned biomechanical measures all increase to attenuate impact forces during landing phase. While average frontal and transverse plane moment, which were consistent with previously reported values [39, 40], were found to be statistically different between heights with moderate and small effect size, respectively, the values were smaller than those experienced by young adults in sport setting (abduction moment 1.3 Nm/kg and external rotation moment 0.2 Nm/kg) [41, 42]; and likely not clinically relevant.…”
Section: Discussionsupporting
confidence: 87%
“…The aforementioned biomechanical measures all increase to attenuate impact forces during landing phase. While average frontal and transverse plane moment, which were consistent with previously reported values [39, 40], were found to be statistically different between heights with moderate and small effect size, respectively, the values were smaller than those experienced by young adults in sport setting (abduction moment 1.3 Nm/kg and external rotation moment 0.2 Nm/kg) [41, 42]; and likely not clinically relevant.…”
Section: Discussionsupporting
confidence: 87%
“…According to previous kinematic studies, landing with the toe-in position due to increased hip adduction, internal knee rotation, knee abduction and knee valgus may increase the risk of ACL injuries, and athletes have been recommended not to do jump-landing with this pattern (13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that landing with the toein position may be accompanied by an increase in the in- ternal torsion of the tibia and knee valgus (12), and increased hip adduction, internal rotation and knee abduction may predispose the knee to ACL injuries (13,14) and may therefore be considered a risk factor for ACL injuries (15).…”
Section: Introductionmentioning
confidence: 99%
“…Foot progression angle (FPA), or the angular difference between the long axis of the foot and the mid-sagittal plane of an individual at initial contact during drop landing, is a modifiable variable of ACL injury risk [26,34] that can affect lower extremity kinematics and kinetics. Padua et al [26] included landing with an FPA greater than 30° toe-in or toe-out as a "high risk" position in the Landing Error Scoring System (LESS).…”
Section: Introductionmentioning
confidence: 99%
“…Other research has stated that just excessive toe-out landing leads to increased knee abduction and external rotation angle, thus having the potential to impinge the ACL against the lateral wall of the femoral intercondylar notch, causing injury [10]. Tran et al [34] has shown that landing with a toe-in position of 30° from neutral (0° FPA) increases peak hip adduction, knee internal rotation angles and moments, as well as peak knee abduction angle, and decreases peak hip flexion angle. Conversely, they demonstrated that landing with a toe-out position decreased these variables resulting in a safer landing position and potentially reducing the risk of ACL injury [34].…”
Section: Introductionmentioning
confidence: 99%